The control of penny fern in tea through pruning and herbicides - Sobar Darana (Jurnal Penelitian Teh dan Kina, 2011)
Study on the control of penny fern in tea through pruning and herbicides was conducted in Pasir Sarongge Experimental Garden, 1.100 m asl from August to November 2010. Experimental design used was split plot design, consisted of three main plots and six subplots. The main plot (pruning height) consisted of (A) 40 cm pruning height, (B) 55 cm pruning height, and (C) 70 cm pruning height. The subplot (method of weed control), consisted of: (1) glyphosate herbicide at 6 liters/ha, (2) paraquat dichloride herbicide, at 4 liters/ha, (3) 2,4-D herbicide, at 3-3 liters/ha, (4) a combination of glyphosate herbicide + 2,4-D at 6 liters/ha, (5) a combination of glyphosate and picloram herbicides, at 4 liters/ha, and (6) manual control of the fern. The total treatment combination was 18 treatments. Each treatment was repeated twice. Observations were made on weed biomass and the growth of tea plants. Weed biomass were observed 3 times with 2-weeks interval, starting at 2 weeks after treatment of weed control.  The growth of tea plants was observed  trought the number of primary shoots. The results showed that  the 40 cm as well as 55 cm pruning height were provided better effectivity compared to 70 cm pruning height. At the third observation, the effectiveness of manual control was similar to the treatment of chemical control, except the treatment of  single 2,4-D. The number of primary shoots  grew on bush after 70 cm pruning height were higher and significantly different compared to the 40 cm pruning height as well as 55 cm pruning height. In every observations, the highest number of primary shoots per bush were consistently obtained from the treatment of combination of  glyphosate and 2,4-D herbicides.